Lithium disilicate glass ceramic compositions and methods thereof
By introducing aphalastin or siliconite in the glass ceramic composition to form a lithium siliconicate and these sub -phase compositions, the existing lithium silicone glass ceramics in bone restoration is insufficient mechanical strength and low biological activity. The problem of glass ceramic composition with high mechanical strength and biological activity.
Patent Information
- Application Number
- CN202411467451.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-05-27
- Filing Date
- 2017-05-25
- Publication Date
- 2025-01-21
AI Technical Summary
Existing lithium disilicate glass ceramics are insufficient in bone repair and have low biological activity, making it difficult to replace bioceramics based on apatite and wollastonite.
A set of glass ceramic compositions have been developed, which contains lithium siliconate as the main crystal phase and aphamium or silicon ash as the secondary phase. By optimizing the ingredients and ceramic technology, the mechanical strength and biological activity of the composition is improved.
The high mechanical strength and biological activity of the glass-ceramic composition is achieved, which is suitable for hard tissue regeneration, especially in bone repair.
Smart Images

Figure CN119330600A_ABST
Abstract
Description
[0001] This invention patent application is a divisional application of the invention patent application with international application number PCT / US2017 / 034421, international application date May 25, 2017, application number 201780032893.X entering the Chinese national phase, and invention name “Lithium disilicate glass ceramic composition and method thereof”.
[0002] This application claims priority under 35 U.S.C. §119 to U.S. Provisional Application Serial No. 62 / 342,381, filed on May 27, 2016, the contents of which are hereby relied upon and incorporated herein by reference in their entirety.
[0003] CROSS-REFERENCE TO RELATED APPLICATIONS
[0004] This application is related to the following commonly owned and assigned USSN provisional applications filed concurrently:
[0005] 62 / 342384, entitled “BIOACTIVE ALUMINOBORATE GLASSES”;
[0006] 62 / 342377, entitled MAGNETIZABLE GLASSCERAMIC COMPOSITION AND METHODS THEREOF;
[0007] 62 / 342391, entitled “BIODEGRADABLE MICROBEADS”;
[0008] 62 / 342411, entitled “BIOACTIVE GLASS MICROSPHERES”;
[0009] 62 / 342,426, entitled "BIOACTIVE BOROPHOSPHATE GLASSES", but the present application does not claim priority from the above document.
[0010] This application is also related to (but does not claim priority to) commonly owned and assigned USSN Application No. 62 / 189,880, filed on July 7, 2015, entitled "ANTIMICROBIAL PHASE-SEPARATING GLASS AND GLASS CERAMIC ARTICLES AND LAMINATES", which mentions copper-containing laminates having a degradable phase and a non-degradable phase capable of releasing copper ions, and 61 / 874,870, filed on September 6, 2013, entitled "High strength glass-ceramics having lithium disilicate and beta-spodumene structures".
[0011] The entire disclosure of each publication or patent document mentioned herein is incorporated herein by reference. background
[0012] The present disclosure relates to glass-ceramic compositions, bioactive glass-ceramic compositions, and articles made from these glass-ceramic compositions, and to methods of making and using these bioactive glass-ceramic compositions and articles.
[0013] Overview
[0014] In some embodiments, the present disclosure provides a set of glass-ceramic compositions, each of which has lithium disilicate as a first major crystalline phase and at least one of the following substances as a second phase: wollastonite, fluorapatite, cristobalite, β-quartz, lithiophosphate, or a combination thereof.
[0015] In some embodiments, the disclosed composition may include the following raw materials, based on the total amount of 100 wt % of the composition: for example, 50 to 75 wt % of SiO2, 1 to 5 wt % of Al2O3, 1 to 8 wt % of P2O5, 2 to 10 wt % of CaO, 5 to 20 wt % of Li2O, 0.5 to 5 wt % of Na2O, 0.5 to 8 wt % of ZrO2, and 0.1 to 1.0 wt % of F - (i.e., fluoride ion).
[0016] In some embodiments, the disclosed composition may further include the following raw materials: for example, 0.1 to 10 wt % of B2O3, based on 100 wt % of the total amount of the composition.
[0017] In some embodiments, the present disclosure provides a glass-ceramic composition or a glass-ceramic article made from the composition having both high strength and high toughness.
[0018] In some embodiments, the present disclosure provides a glass-ceramic composition having excellent biocompatibility.
[0019] In some embodiments, the present disclosure provides methods of making and using the disclosed compositions. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In an embodiment of the present disclosure:
[0021] Figure 1 X-ray diffraction spectra are shown for Example compositions 7 to 10. All samples were ceramized using a cycle of 700°C for 2 hours followed by 800°C for 4 hours.
[0022] Figure 2 A to 2D show the Figure 2 A, 2B, 2C and 2D correspond to SEM images of the polished surfaces of Example compositions 7 to 10.
[0023] Figure 3 A to 3D show the Figure 3 A, 3B, 3C and 3D correspond to confocal SEM images of MC3T3 cell growth in disclosed compositions 7 to 10.
[0024] Figure 4 A and 4B show the first day attachment and proliferation of MC3T3 cells on the disclosed bioactive glass-ceramic discs: absolute levels (absolute cell number; 4A) and relative to in vitro culture control examples: Tissue Culture Relative levels of (TCT) (tissue culture treated) wells (relative cell number; 4B).
[0025] Figure 5 A and 5B show the cell proliferation results for disclosed compositions 7 to 10. Detailed Description
[0026] Various embodiments of the present disclosure are described in detail below with reference to the accompanying drawings (if any). Reference to various embodiments does not limit the scope of the present disclosure, which is limited only by the scope of the appended claims. In addition, any examples listed in this specification are not limiting and only list some of the many possible embodiments of the claimed invention.
[0027] In some embodiments, the disclosed methods of manufacture and use provide one or more advantageous features or aspects, including, for example, the features and aspects described below. Features or aspects listed in any claim are generally applicable to all aspects of the invention. Any single or multiple features or aspects described in any claim may be combined with or replaced with any other features or aspects described in any one or more other claims.
[0028] definition
[0029] "Glass," "glasses," or similar terms may refer to glass or glass-ceramic.
[0030] "Glass article" or similar terms may refer to any object made in whole or in part from the disclosed glasses or glass-ceramics.
[0031] "Biological activity index", "Biological activity index", "I B " or similar terms or symbols represent, for example, the time required for more than 50% of the interface of a particular bioactive material to be connected to a biological material (such as bone, tissue, and the like). Mathematically, the bioactivity index (according to Hench; see Cao, W. et al., Bioactive Materials, Ceramics International, 1996, No. 22, pp. 493-507) is 1 B =100 / t 0.5bb , where t 0.5bb More than 50% of the bioactive material interface (e.g., implant) with biomaterials [e.g., bone, tissue, and similar materials, including osteogenic materials (category A with intracellular and extracellular responses, such as 45S5 ) and osteoconductive materials (category B where extracellular response occurs only at the interface, such as synthetic hydroxyapatite)] are connected.
[0032] The terms "include", "comprising" or similar terms mean including but not limited to, that is, inclusive rather than exclusive.
[0033] "About" used to describe modifications of embodiments of the present disclosure, such as the amount of an ingredient in a composition, concentration, volume, process temperature, process time, yield, flow rate, pressure, viscosity, and other numerical values and their ranges, or component size, and other numerical values and their ranges, refers to quantitative variations that may occur, for example, in typical assays and processing steps for preparing materials, compositions, compounds, concentrates, component parts, manufacture of articles, or application of formulations; inadvertent errors in these steps; differences in the manufacture, source, or purity of raw materials or ingredients used to perform the methods; and similar considerations. The term "about" also includes amounts that vary from a specific initial concentration or mixture due to aging of the composition or formulation, as well as amounts that vary from a specific initial concentration or mixture due to mixing or processing of the composition or formulation.
[0034] "Optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0035] As used herein, the indefinite articles "a" or "an" and the corresponding definite articles "the" mean at least one, or one or more, unless stated otherwise.
[0036] Abbreviations familiar to those of ordinary skill in the art may be used (e.g., "h" or "hrs" for hours, "g" or "gm" for grams, "mL" for milliliters, "rt" for room temperature, "nm" for nanometers, and the like).
[0037] The specific and preferred numerical values and ranges disclosed in components, ingredients, additives, scales, conditions, time and the like are only for illustration, and they do not exclude other limited numerical values or other numerical values within the limited range. The compositions and methods of the present disclosure may include any numerical value or any combination of numerical values, specific numerical values, more specific numerical values and preferred numerical values described herein, including explicit or implicit intermediate values and intermediate ranges.
[0038] Bioactive materials with high strength and toughness are highly desirable for use, for example, in the regeneration of bones and teeth. Lithium disilicate-based glass-ceramics are able to provide highly desirable mechanical properties, including high bulk strength and fracture toughness, due to their microstructure of randomly oriented interlocking crystals. Fracture toughness values range from 2 to 3 MPa·m 1 / 2Glass ceramics can be realized in glass ceramic systems based on lithium disilicate compositions (see commonly owned and assigned USSN 61 / 874870). Lithium disilicate glass ceramics have been widely used to make single or multiple tooth restorations. However, these glass ceramics have not been used in bone repair because they have relatively low bioactivity. In contrast, bioceramics based on apatite and wollastonite have been shown to have high bioactivity, but do not have sufficient mechanical strength compared to, for example, cortical bone (Hench, LL, "Bioceramics", Journal of the American Ceramic Society, 1998, No. 81: 1705-1728).
[0039] In some embodiments, the present disclosure provides a group of glass-ceramic compositions having phase aggregates (assemblage) containing a lithium disilicate major phase and one or more minor phases such as apatite or wollastonite. These superior compositions exhibit an excellent combination of high mechanical strength and high bioactivity, making them very suitable for hard tissue regeneration.
[0040] WO 2015200017 ('017), entitled "Process for producing a sintered lithium disilicate glass ceramic dental restoration and kit of parts", mentions a method for producing a sintered lithium disilicate glass ceramic dental restoration using a porous three-dimensional article. In contrast, the composition disclosed herein has different phase aggregates, for example, the disclosed composition has lithium disilicate and apatite, while '017 has only lithium disilicate, and the composition disclosed herein is bioactive, while the composition of '017 is not bioactive. In addition, the composition disclosed herein has CaO and F - , to form apatite phase.
[0041] US20150087493 mentions lithium disilicate apatite glass ceramics, which are characterized by high chemical stability and can be used as restorative materials in dentistry. However, these materials all contain K2O, which is not present in the composition disclosed herein.
[0042] US 7166548 mentions an apatite glass ceramic containing at least one glass phase and at least one apatite phase, and characterized in that at least one of the apatite phases is a phosphate-free and fluorine-free silicon oxyapatite phase. However, these materials do not contain the phosphates and fluorine present in the compositions disclosed herein.
[0043] In some embodiments, the present disclosure provides a glass-ceramic composition comprising:
[0044] a first crystalline phase, the first crystalline phase comprising lithium disilicate;
[0045] A second crystalline phase, wherein the second crystalline phase is selected from the group consisting of at least one of the following substances: wollastonite, fluoroapatite, cristobalite, β-quartz, pyroxenite, or a combination thereof.
[0046] In some embodiments, the present disclosure provides a glass-ceramic composition, wherein the first crystalline phase and the second crystalline phase together comprise the following raw materials, based on 100 wt % of the total amount of the composition:
[0047] 50 to 75 wt. % SiO2;
[0048] 1 to 5 wt% Al2O3;
[0049] 1 to 8 wt.% P2O5;
[0050] 2 to 10 wt.% CaO;
[0051] 5 to 20 wt% Li2O;
[0052] 0.5 to 5 wt% Na2O;
[0053] 0.5 to 8 wt % ZrO2; and
[0054] 0.1 to 1.0 wt% F - (i.e., fluoride ion).
[0055] In some embodiments, the glass ceramic composition may further include the following raw materials: for example, 0.1 to 10 wt % of B 2 O 3 , based on 100 wt % of the total amount of the composition.
[0056] In some embodiments, based on 100% by weight of the total amount of the composition, the first crystalline phase and the second crystalline phase together comprise the following raw materials:
[0057] 50 to 60 wt.% SiO2;
[0058] 1 to 3 wt% Al2O3;
[0059] 2 to 6 wt% P2O5;
[0060] 4 to 8 wt.% CaO;
[0061] 7.5 to 12.5 wt.% Li2O;
[0062] 0.5 to 2 wt% Na2O;
[0063] 1 to 4 wt % ZrO2; and
[0064] 0.2 to 0.8 wt% F - .
[0065] In some embodiments, the above composition may be a preferred or most preferred composition, and may include, consist of, or consist essentially of the above composition components.
[0066] In some embodiments, the disclosed bioactive compositions and preparations may be preferred or most preferred compositions or preparations, and may comprise, consist of, or consist essentially of the disclosed bioactive compositions or preparations.
[0067] In some embodiments, the disclosed methods of making and using may be the preferred or most preferred methods, and may comprise, consist of, or consist essentially of the disclosed methods.
[0068] In some embodiments, the composition can have a high strength of 200 MPa to 500 MPa, such as at least 200 MPa, at least 300 MPa, or at least 400 MPa, including intermediate values and ranges.
[0069] In some embodiments, the composition may have a viscosity of 1.4 to 2.0 MPa·m 1 / 2 , for example at least 1.4, 1.6, 1.8 or 2.0 MPa·m 1 / 2 High fracture toughness, including intermediate values and ranges.
[0070] In some embodiments, the composition has both a high strength of 200 MPa to 500 MPa and a low strength of 1.4 to 2.0 MPa·m 1 / 2 High fracture toughness.
[0071] Precursor glass
[0072] In some embodiments, the composition can be prepared from a precursor glass composition comprising, for example, the following raw materials: based on 100 wt % of the total amount of the composition,
[0073] 50 to 75 wt. % SiO2;
[0074] 1 to 5 wt% Al2O3;
[0075] 1 to 8 wt.% P2O5;
[0076] 2 to 10 wt.% CaO;
[0077] 5 to 20 wt% Li2O;
[0078] 0.5 to 5 wt% Na2O;
[0079] 0.5 to 8 wt % ZrO2; and
[0080] 0.1 to 1.0 wt% F - .
[0081] In some embodiments, the precursor glass composition described above does not undergo significant changes after ceramization.
[0082] In some embodiments, the present invention provides a method for making the above-mentioned glass-ceramic composition, the method comprising, for example:
[0083] The precursor glass is ceramized by heating it at 650° C. to 750° C. for 0.5 to 10 hours and then heating it at 750° C. to 850° C. for 0.5 to 20 hours, and the precursor glass comprises the following raw materials based on 100% by weight of the total amount of the composition:
[0084] 50 to 75 wt. % SiO2;
[0085] 1 to 5 wt% Al2O3;
[0086] 1 to 8 wt.% P2O5;
[0087] 2 to 10 wt.% CaO;
[0088] 5 to 20 wt% Li2O;
[0089] 0.5 to 5 wt% Na2O;
[0090] 0.5 to 8 wt % ZrO2; and
[0091] 0.1 to 1.0 wt% F - .
[0092] In some embodiments, the manufacturing method further comprises, for example, performing ion exchange on the obtained glass-ceramic composition to generate at least one compressive stress layer on at least one surface of the article to increase the mechanical strength of the article.
[0093] Bioactive Compositions
[0094] In some embodiments, the present disclosure provides a bioactive composition comprising:
[0095] Glass ceramics, comprising:
[0096] a first crystalline phase, the first crystalline phase comprising lithium disilicate;
[0097] a second crystalline phase selected from the group consisting of at least one of wollastonite, fluorapatite, cristobalite, β-quartz, pyroxenite, or a combination thereof; and
[0098] One or more living osteoblasts, ie, bioactive glass-ceramics comprising the disclosed compositions and cells capable of synthesizing bone.
[0099] In some embodiments, in the above bioactive composition, based on 100% by weight of the total amount of the composition, the glass ceramic composition may include, for example, the following raw materials:
[0100] 50 to 75 wt. % SiO2;
[0101] 1 to 5 wt% Al2O3;
[0102] 1 to 8 wt.% P2O5;
[0103] 2 to 10 wt.% CaO;
[0104] 5 to 20 wt% Li2O;
[0105] 0.5 to 5 wt% Na2O;
[0106] 0.5 to 8 wt % ZrO2; and
[0107] 0.1 to 1.0 wt% F - .
[0108] In some embodiments, the glass ceramic composition may include, for example, the following raw materials, based on 100% by weight of the total amount of the composition:
[0109] 50 to 60 wt.% SiO2;
[0110] 1 to 3 wt% Al2O3;
[0111] 2 to 6 wt% P2O5;
[0112] 4 to 8 wt.% CaO;
[0113] 7.5 to 12.5 wt.% Li2O;
[0114] 0.5 to 2 wt% Na2O;
[0115] 1 to 4 wt % ZrO2; and
[0116] 0.2 to 0.8 wt% F - .
[0117] In some embodiments, the bioactive composition may further comprise, for example, the following raw materials, based on 100% by weight of the total amount of the composition: for example, 0.1 to 10% by weight of B2O3.
[0118] In some embodiments, the present disclosure provides a method of culturing osteoblasts, that is, a method using the disclosed bioactive composition, the method comprising, for example:
[0119] The above-described biologically active composition is contacted with a suitable liquid culture medium.
[0120] In some embodiments, the glass-ceramic composition of the bioactive composition can be combined with or contacted with a suitable liquid culture medium prior to contacting with living osteoblasts.
[0121] In some embodiments, the contacting is capable of causing proliferation of osteoblasts on the surface of the bioactive composition.
[0122] In some embodiments, the contacting is capable of causing osteoblast proliferation in a suitable liquid culture medium (eg, MC3T3 cell culture medium: ie, α-MEM supplemented with 10% fetal bovine serum and 1 mM sodium pyruvate).
[0123] In some embodiments, suitable liquid culture medium may include, for example, simulated body fluid (SBF) compositions. SBF is used to test the apatite formation activity of bioactive glass / glass ceramics. The disclosed bioactive glass ceramics form in situ bioactive apatite layers (mineral phases of bones and teeth) that can be combined with bones and teeth and can even be combined with soft tissues. The potential applications of the disclosed bioactive glass ceramics may include, for example, monolithic products, compositions, films, coatings or similar forms for repairing load-bearing joint bones, tooth regeneration, dentin hypersensitivity treatment, artificial vertebral bodies, spinous spacers, intervertebral spacers, iliac spacers, particle fillers, stents, middle ear implants and other types of small bone replacements, trauma treatment and other applications. The disclosed bioactive glass-ceramics are biocompatible with, for example, osteoblasts, keratinocytes, and human umbilical vein endothelial cells (HUVEC) (see, for example, T. Kokubo et al., "How useful is SBF in predicting in vivo bone bioactivity?", Biomaterials, 27
[15] 2907-15 (2006)).
[0124] In some embodiments, the disclosed compositions and disclosed bioactive compositions can also be used in, for example, angiogenesis (HUVEC cells), wound treatment (keratinocytes), bone tissue engineering (MC3T3 cells), and the like.
[0125] In some embodiments, the disclosed compositions are biocompatible and biologically active (ie, bioactive) with a variety of cell types for use in a variety of applications.
[0126] In some embodiments, the disclosed compositions and methods thereof have advantages in various aspects, including, for example:
[0127] Glass-ceramic compositions have both high strength and high toughness;
[0128] The glass-ceramic composition has excellent biocompatibility; and
[0129] The glass-ceramic composition is capable of supporting the growth and function of osteoblasts.
[0130] In some embodiments, the disclosed bioactive glass-ceramic composition may also include morphological elements selected from, for example, hollow microspheres, solid microspheres, or combinations thereof, i.e., the glass composition has a particle shape such as a sphere, an elongated sphere, or an egg-shaped, rod-shaped, or similar geometric configuration. Table 1 lists representative embodiments of the disclosed composition. The ceramization cycles of all Examples 1 to 15 are 2 hours at 700°C followed by 4 hours at 800°C.
[0131] Table 1. Example compositions (Examples 7 to 15) and control compositions (Control Examples C-1 to C-6).
[0132]
[0133]
[0134] Table 1 (continued)
[0135]
[0136] 1. "C-#" designation represents control examples (i.e., C- to C-6).
[0137] 2. Identification of phase aggregates:
[0138] A = lithium disilicate, cristobalite, wollastonite, β-quartz, pyrophyllite.
[0139] B = lithium disilicate, wollastonite, lithium phosphate ore.
[0140] C = lithium disilicate, lithium metasilicate, wollastonite, lithium phosphate ore.
[0141] D = lithium disilicate, β-quartz, pyrophyllite.
[0142] E = lithium disilicate, cristobalite, fluorapatite, β-quartz.
[0143] F = lithium disilicate, fluoroapatite, β-quartz, pyrophyllite.
[0144] G = lithium disilicate, fluoroapatite, lithium metasilicate, β-quartz.
[0145] H = lithium disilicate, fluorapatite, β-quartz.
[0146] Sample appearance: The samples of Examples 1 to 8 and Examples 10 to 15 are translucent white.
[0147] Example 9: Semi-transparent white.
[0148] In some embodiments, the disclosed compositions may be free (e.g., zero ppm or ppb) or substantially free (e.g., less than a few ppm or ppb of trace amounts) of at least one of the following substances, for example: K2O, K2CO3, Ca3(PO4)2, MgO, TiO2, As2O3, Sb2O3, or combinations or mixtures thereof.
[0149] In some embodiments, the present disclosure provides a precursor glass composition that can be ceramized to produce glass ceramics with excellent mechanical properties and biocompatibility. In some embodiments, the present disclosure provides glass ceramics having high mechanical strength by forming an interlocking structure in the ceramized article that forces cracks to propagate along a tortuous path. In addition, the presence of secondary crystalline phases such as fluorapatite and wollastonite in the disclosed compositions is beneficial to the growth, proliferation and function of osteoblastic cell lines.
[0150] In some embodiments, the precursor glass or raw material glass may include the following raw materials, for example, 50 to 75 wt % of SiO2, 1 to 5 wt % of Al2O3, 5 to 20 wt % of Li2O, 0.5 to 5 wt % of Na2O, 0.5 to 8 wt % of ZrO2, and 0.1 to 1.0 wt % of F, based on the total amount of the composition 100 wt %. - In some embodiments, a more preferred precursor glass composition may be, for example, 50 to 60 wt% SiO2, 1.0 to 3.0 wt% Al2O3, 0.1 to 4.0 wt% B2O3, 7.5 to 12.5 wt% Li2O, 0.5 to 2.0 wt% Na2O, 1.0 to 4.0 wt% ZrO2, and 0.2 to 0.8 wt% F2O3, based on 100 wt% of the total amount. - ions (see Table 1).
[0151] In some embodiments, the precursor glass can be ceramized into a glass ceramic product having a high crystallinity of, for example, 80% or more (e.g., 80% to 95%). The primary crystalline phase comprises lithium disilicate. The secondary crystalline phase may comprise, for example, fluoroapatite, wollastonite, cristobalite, β-quartz, pyroxenite, or a mixture thereof, depending on the target composition.
[0152] With reference to the accompanying drawings, Figure 1 The X-ray diffraction spectra of Example compositions 7 to 10 are shown, wherein the marking numbers 7, 8, 9 and 10 correspond to Example compositions 7 to 10 in Table 1, respectively. The following significant peaks (with marked shapes) are identified: lithium disilicate (asterisk), lithium metasilicate (triangle), fluoroapatite (dot), β-quartz (square) and cristobalite (diamond). All samples are ceramicized using a cycle of 700°C, 2 hours followed by 800°C, 4 hours.
[0153] In some embodiments, the disclosed glass-ceramic articles comprising interlocked lithium disilicate can be readily obtained by ceramizing the precursor glass for a period of time at a temperature of 700° C. to 900° C. The grain size of the lithium disilicate phase can be greater than 1 micron and have a high aspect ratio typically formed in glass-ceramics. Figure 2 A to 2D show the Figure 2 SEM images of polished surfaces of Example compositions 7 to 10 corresponding to A, 2B, 2C and 2D. All samples were ceramized using a cycle of 700°C for 2 hours followed by 800°C for 4 hours. Before observation, the samples were etched in 1% HF for one minute.
[0154] While not wishing to be bound by theory, it is believed that the presence of interlocking crystals may be an important factor in establishing strengthening mechanisms including crack deflection and tortuous crack paths that may contribute to the observed high fracture strength and high flexural strength (Table 1). For example, it is believed that strengths in excess of 1.5 MPa·m 1 / 2 The fracture toughness is over 300MPa and the flexural strength is over 300MPa.
[0155] In some embodiments, the disclosed glass-ceramic products or residual glass can be ion exchanged to generate a compressive stress layer on the surface of the vessel to further improve the mechanical strength.
[0156] In some embodiments, the disclosed glass-ceramic compositions exhibit excellent biocompatibility. Cell attachment on the surface of compositions 7 to 9 was clearly observed in the confocal images. MC 3T3 cells were cultured for one day, fixed with 4% formaldehyde, and then stained with Alexa Fluor 568 phalloidin and DAPI before confocal photography. Figure 3 A to 3D show the Figure 3 Confocal SEM images of MC3T3 cells grown in disclosed compositions 7 to 10 corresponding to A, 3B, 3C and 3D. All samples were ceramized using a cycle of 700°C for 2 hours followed by 800°C for 4 hours. Cells were cultured for one day, fixed with 4% formaldehyde, and then stained with AlexaFluor 568 phalloidin and DAPI before confocal photography.
[0157] By Figure 5 A) and at relative levels relative to the TCT control ( Figure 5 B) to demonstrate the ability of the disclosed glass ceramics of Example compositions 7 to 10 to support cell proliferation. MCT3 cells were cultured on glass ceramic discs. On the fourth and seventh days, the cells were digested overnight at 65°C with digestion buffer (125 μg / ml papain, 2 mM L-cysteine, 2 mM EDTA) and the Quant-iT TM The amount of dsDNA was measured using a dsDNA kit (Thermo Fisher). The increase in DNA concentration with increasing incubation time provides additional evidence that the disclosed composition has excellent biocompatibility.
[0158] In some embodiments, the disclosed glass-ceramics can be manufactured using thin rolling, float, casting, and similar methods, and scaffolds can be produced using methods such as rapid prototyping, polymer foam replication, particle sintering, and the like. Glass-ceramics with desired morphology can be used to support cell growth and hard tissue regeneration.
[0159] In some embodiments, glass composition can affect the mechanical strength, biocompatibility and biodegradation of the disclosed composition realized.In some embodiments, disclosed glass composition can also include: for example, SiO , for precursor glass, it is as the main oxide forming glass, and can play the effect of stabilizing glass and glass-ceramic network structure.In some embodiments, SiO concentration should be high enough, to form the effect of lithium disilicate crystalline phase when precursor glass is heat-treated to be converted into glass-ceramic (that is, ceramization).However, these glasses can not contain too much SiO , because pure SiO or high SiO glass has undesirable high melting temperature (200 poise temperature).In some embodiments, glass or glass-ceramic composition can include for example 60 to 82 % by weight SiO , based on gross weight 100 % by weight.
[0160] In some embodiments, Al2O3 can also provide a stabilizing effect on the network structure. Al2O3 is beneficial for improving mechanical properties and chemical durability. However, too much Al2O3 generally increases the viscosity of the melt and reduces the proportion of lithium disilicate crystals to a point where an interlocking structure cannot be formed. It is preferred to keep the concentration of Al2O3 within a reasonable range, such as 1 to 5 weight percent.
[0161] In some embodiments, the addition of B2O3 can be beneficial in improving the crack resistance of the glass-ceramic, which is helpful for dental applications. In addition, higher boron concentrations can increase the degradation rate of the bioactive composition, which may be required for applications such as bone regeneration.
[0162] Li2O is another important component in the disclosed precursor glass composition. Li2O is conducive to the formation of lithium disilicate crystalline phase. The content of Li2O is required to be at least 8 wt% Li2O to obtain a glass-ceramic with lithium disilicate as the main phase. However, when the Li2O content becomes too high (e.g., greater than 15 wt%), the precursor glass becomes very fluid, has a low resistivity, and is difficult to melt or form.
[0163] In some embodiments, the disclosed glass and glass-ceramic compositions may include, for example, 2 to 6 wt % P2O5, for example as a nucleating agent, to allow bulk nucleation to occur. If the concentration of P2O5 is too low, for example less than 2 wt %, the precursor glass will not crystallize. If the concentration of P2O5 is too high, for example greater than 6 wt %, it may be difficult to control devitrification after cooling during the precursor glass forming process.
[0164] In some embodiments, divalent cation oxides such as alkaline earth metal oxides may also be used to improve the melting characteristics and bioactivity of the glass. For example, it has been found that CaO and P2O5 are combined to form apatite, or CaO and SiO2 are combined to form wollastonite. Apatite and wollastonite are both known bioactive ceramics (see Hench, LL, supra).
[0165] In some embodiments, the Na2O comprising 0.1 to 5 wt % of the amount in the precursor glass can reduce the melting temperature of the precursor glass, and can shorten the ceramicization cycle. In addition, if it is desired to have a higher coefficient of thermal expansion (i.e., CTE) in the glass-ceramic product, the Na2O comprising in the precursor glass can also increase the coefficient of thermal expansion after ceramicization.
[0166] In some embodiments, melting may be accomplished at elevated temperatures, such as above 1300° C., to fuse the precursor glass materials. In some embodiments, ceramizing is a heat treatment of the molten glass to crystallize the glass into a glass-ceramic material. Example
[0167] The following examples demonstrate the manufacture, use, and analysis of the disclosed compositions, as well as methods following the general procedures described above.
[0168] Example 1
[0169] Preparation of Comparative Examples C-1 to C-6 and Practical Example Glass-Ceramic Compositions 7 to 15 The comparative examples and practical example glass-ceramic compositions 1 to 15 are listed in Table 1, and their respective glass raw materials including, for example, dioxide, boric acid, alumina, lithium carbonate, sodium carbonate, limestone, spodumene, aluminum metaphosphate were combined and melted in an electric furnace in the specified amounts. The mixer vigorously mixes the precursor glass raw materials in a plastic jar. Subsequently, the mixture is transferred to a platinum crucible with an inner volume of about 650cc and heated at 700°C for 2 hours, then at 800°C for 4 hours, and then the glass melt is poured onto a steel plate and annealed at 500°C.
[0170] Example 2
[0171] Preparation of glass ceramic discs Glass ceramic discs were prepared by ceramizing parts. The precursor glass frit cake was ceramized using the following cycle in an electric furnace: 2 hours at 700°C for nucleation, followed by 4 hours at 800°C for crystal growth. After ceramization, a diamond drill was used to drill the core to obtain a disc (12.5 mm diameter × 2.0 mm thickness), which was then ground and polished to a 1.0 micron finish using CeO2 slurry. All finished discs were cleaned by sonication in an ultrasonic sonicator for 10 minutes.
[0172] Example 3
[0173] Method for attaching and growing bone cells using the bioactive composition of Example 1 The glass ceramic disc of Example 2 (made from the composition of Processing Example 1 above) was placed in a 24-well microplate that had been well treated for tissue culture. Each composition had a replicate disc. Then, MC 3T3 cells (at 20K / 2mL) were seeded into these wells and some wells without any discs (control examples that had been treated for tissue culture (TCT)). The microplates were cultured for one, four, or seven days. The cells in the microplates that had been cultured for one day were fixed with 4% formaldehyde and then stained with Alexa Fluor 568 phalloidin and DAPI before confocal photography.
[0174] Figure 4 A and 4B show the relative bioactive glass control composition 1 (C-1) and in vitro culture control example: Tissue Culture (TCT) wells: Day 1 attachment and proliferation of MC3T3 cells on disclosed bioactive glass-ceramic discs of Example compositions 7, 8, 9 and 19 (see Table 1) at both absolute level (absolute cell number; 4A) and relative level (relative cell number; 4B).
[0175] Figure 5 A and 5B show the cell proliferation results of the disclosed compositions 7 to 10. The cells in the culture plates on the fourth day (D4) and the seventh day (D7) were digested for 16 hours at 65°C with a digestion buffer solution (125 μg / ml papain, 2 mM L-cysteine, 2 mM EDTA) and the Quant-iT TM The amount of dsDNA was measured by a dsDNA kit (Thermo Fisher Scientific Inc.). The increase in DNA concentration with increasing incubation time provided additional evidence of their excellent biocompatibility.
[0176] MC3T3 cells were digested with papain and the amount of DNA was measured using the PicoGreen assay. D4 or D7 refers to day 4 or day 7 (as in "day 4 or day 7 of cell culture"). TCT refers to a 100 μM 100 μM tube purchased from Corning, Inc. ) purchased tissue culture treated microplates. Glass ceramic discs were placed in 24-well well tissue culture treated microplates. Each composition had a replicate disc. MC 3T3 cells (at 20K / 2mL) were then seeded into these wells and some wells without any discs (TCT control). The microplates were cultured for four or seven days. On the fourth and seventh days, the cells were digested with digestion buffer (D-PBS containing 125 micrograms / mL of papain, 2mM L-cysteine, 2mM EDTA) at 65°C in a humid environment with shaking (60rpm). An attempt was made to remove dissolved DNA from the glass ceramic discs by pipetting the digestion solution up and down the discs. The collected digestion solution was briefly centrifuged to remove any residual particles. Using Quant-iT TM The amount of dsDNA in the supernatant was measured using a dsDNA kit (Thermo Fisher Scientific Inc.) according to the manufacturer's instructions.
[0177] Material:
[0178] MC3T3E1 subclone 14 ( CRL2594 TM) (see atcc.org / products / all / CRL-2594.aspx).
[0179] Quant-iT TM dsDNA kit (Invitrogen, #P11496). This kit contains Quant-iT TM dsDNA reagent (10 vials, each containing 100 μL aliquots), 25 mL of 20X TE buffer, 1 mL of 100 μg / mL λDNA (dsDNA standard), papain (Sigma-Aldrich, #P4762-25MG), L-cysteine (Sigma-Aldrich, #C1276-10G), EDTA (Sigma-Aldrich, #E6511), D-PBS (Thermo Fisher Scientific, #14190), shaker set to 65°C and plate reader.
[0180] The disclosure has been described with reference to various specific embodiments and techniques. However, it should be appreciated that many variations and modifications can be made within the scope of the disclosure.
Claims
1. A glass-ceramic composition comprising: a first crystalline phase, the first crystalline phase comprising lithium disilicate; and a second crystalline phase, the second crystalline phase comprising pyroxenite, in, Based on 100% by weight of the total amount of the composition, the first crystalline phase and the second crystalline phase together comprise the following raw materials: 50 to 75 wt. % SiO2; 1 to 5 wt% Al2O3; 1 to 8 wt.% P2O5; CaO; as well as At least 8 wt.% Li2O.
2. The glass-ceramic composition according to claim 1, characterized in that Based on 100% by weight of the total amount of the composition, the first crystalline phase and the second crystalline phase together comprise the following raw materials: 65 to 75 wt. % SiO2; 1 to 3 wt% Al2O3; 1 to 6 wt. % P2O5; up to 10 wt.% CaO; at least 8 wt.% Li2O; Up to 2 wt.% Na2O; 0.5 to 8 wt % ZrO2; and 0.1 to 1.0 wt% F - .
3. The glass-ceramic composition according to claim 1, characterized in that Based on the total amount of 100 wt % of the composition, the following raw materials are further included: 0.1 to 10 wt % of B2O3.
4. The glass-ceramic composition according to claim 1, characterized in that Based on 100 wt % of the total amount of the composition, the following raw materials are further included: greater than 0 to 10 wt % of CaO.
5. The glass-ceramic composition according to claim 1, characterized in that Based on 100 wt % of the total amount of the composition, the following raw materials are further included: 2 to 10 wt % of CaO.
6. The glass-ceramic composition according to claim 1, characterized in that Based on 100 wt % of the total amount of the composition, the following raw materials are further included: 8 to 20 wt % of Li2O.
7. The glass-ceramic composition according to claim 1, characterized in that Based on 100 wt % of the total amount of the composition, the following raw materials are further included: 0.5 to 2 wt % of Na2O.
8. The glass-ceramic composition according to claim 1, characterized in that Based on the total amount 100 wt % of the composition, the following raw materials are further included: 1 to 8 wt % of ZrO 2 .
9. The glass-ceramic composition according to any one of claims 1 to 8, characterized in that Based on the total amount 100 wt % of the composition, the following raw materials are further included: 2 to 6 wt % of P2O5.
10. The glass-ceramic composition according to any one of claims 1 to 8, characterized in that The composition has a high strength of 200 MPa to 500 MPa.
11. The glass-ceramic composition according to any one of claims 1 to 8, characterized in that The composition has a strength of 1.4 to 2.0 MPa·m 1 / 2 High fracture toughness.
12. A glass ceramic product comprising: The glass ceramic composition according to any one of claims 1 to 8; and A compressive stress layer is formed on at least one surface of the glass-ceramic article by ion exchange.
13. A glass ceramic product comprising: a first crystalline phase, the first crystalline phase comprising lithium disilicate; a second crystalline phase, the second crystalline phase comprising pyroxenite; forming a compressive stress layer on at least one surface of the glass-ceramic article by ion exchange; and A glass ceramic composition, based on 100% by weight of the total amount of the composition, comprising: 65 to 75 wt.% SiO2; 1 to 3 wt% Al2O3; 8 to 20 wt% Li2O; 1 to 8 wt % P2O5; and 2 to 8 wt. % ZrO2.
14. The glass-ceramic product according to claim 13, characterized in that The glass ceramic composition includes greater than 0 to 10 wt % of CaO, based on 100 wt % of the total amount of the composition.
15. The glass-ceramic product according to claim 13, characterized in that The glass ceramic composition includes up to 10 wt % of CaO, based on 100 wt % of the total amount of the composition.
16. The glass ceramic product according to any one of claims 13 to 15, characterized in that The composition has a high strength of 200 MPa to 500 MPa.
17. The glass ceramic product according to any one of claims 13 to 15, characterized in that The composition has a strength of 1.4 to 2.0 MPa·m 1 / 2 High fracture toughness.
18. A glass composition, comprising, based on 100 wt % of the total amount of the composition: 50 to 75 wt. % SiO2; 1 to 5 wt% Al2O3; 1 to 8 wt.% P2O5; CaO; and At least 8 wt.% Li2O.
19. The glass composition according to claim 18, wherein Based on 100% by weight of the total amount of the composition, it comprises: 65 to 75 wt.% SiO2; 1 to 3 wt% Al2O3; 1 to 6 wt. % P2O5; up to 10 wt.% CaO; at least 8 wt.% Li2O; Up to 2 wt.% Na2O; 0.5 to 8 wt % ZrO2; and 0.1 to 1.0 wt% F - .
20. The glass composition according to claim 18, wherein Based on 100% by weight of the total amount of the composition, it comprises: 65 to 75 wt.% SiO2; 1 to 3 wt% Al2O3; 8 to 20 wt% Li2O; 1 to 8 wt % P2O5; and 2 to 8 wt. % ZrO2.
21. The glass composition according to claim 18, wherein The composition includes more than 0 to 10 wt % of CaO based on 100 wt % of the total amount.
22. The glass composition according to claim 18, wherein It contains up to 10 wt % of CaO, based on 100 wt % of the total amount of the composition.
23. The glass composition according to any one of claims 18 to 22, wherein: When the glass is heated at 650° C. to 750° C. for 0.5 to 10 hours and then at 750° C. to 850° C. for 0.5 to 20 hours, a first crystalline phase including lithium disilicate and a second crystalline phase including pyrophorite are formed.
24. A bioactive composition comprising: a first crystalline phase, the first crystalline phase comprising lithium disilicate; a second crystalline phase, the second crystalline phase comprising pyroxenite, in, Based on 100% by weight of the total amount of the composition, the first crystalline phase and the second crystalline phase together comprise the following raw materials: 50 to 75 wt. % SiO2; 1 to 5 wt% Al2O3; 1 to 8 wt.% P2O5; CaO; as well as At least 8 wt.% Li2O.
25. The bioactive composition of claim 24, wherein The bioactive composition combines with osteoblasts to enable bone synthesis.
26. The bioactive composition of claim 24, wherein The osteoblasts are capable of proliferating when contacted with the bioactive composition in a simulated body fluid.
27. The bioactive composition according to any one of claims 24 to 26, characterized in that Based on 100% by weight of the total amount of the composition, it comprises: 65 to 75 wt.% SiO2; 1 to 3 wt% Al2O3; 1 to 6 wt. % P2O5; up to 10 wt.% CaO; at least 8 wt.% Li2O; Up to 2 wt.% Na2O; 0.5 to 8 wt % ZrO2; and 0.1 to 1.0 wt% F - .
28. The bioactive composition according to any one of claims 24 to 26, characterized in that Based on 100% by weight of the total amount of the composition, it comprises: 65 to 75 wt.% SiO2; 1 to 3 wt% Al2O3; 8 to 20 wt% Li2O; 1 to 8 wt % P2O5; and 2 to 8 wt. % ZrO2.
29. The bioactive composition according to any one of claims 24 to 26, characterized in that The composition includes more than 0 to 10 wt % of CaO based on 100 wt % of the total amount.
30. The bioactive composition according to any one of claims 24 to 26, characterized in that It contains up to 10 wt % of CaO, based on 100 wt % of the total amount of the composition.
31. A method for making a glass-ceramic composition, the method comprising: The precursor glass composition is ceramized by heating the mixture at 650° C. to 750° C. for 0.5 to 10 hours and then heating at 750° C. to 850° C. for 0.5 to 20 hours, wherein the precursor glass composition comprises the following raw materials based on 100% by weight of the total amount of the composition: 50 to 75 wt. % SiO2; 1 to 5 wt% Al2O3; 1 to 8 wt.% P2O5; CaO; and At least 8 wt.% Li2O.
32. The method of claim 31, wherein: The ceramization forms a first crystalline phase comprising lithium disilicate and a second crystalline phase comprising pyroxenite.
33. The method of claim 31, wherein: Based on 100% by weight of the total amount of the composition, the precursor glass composition comprises the following raw materials: 65 to 75 wt.% SiO2; 1 to 3 wt% Al2O3; 1 to 6 wt. % P2O5; up to 10 wt.% CaO; at least 8 wt.% Li2O; Up to 2 wt.% Na2O; 0.5 to 8 wt % ZrO2; and 0.1 to 1.0 wt% F - .
34. The method according to any one of claims 31 to 33, characterized in that Based on 100% by weight of the total amount of the composition, the precursor glass composition comprises the following raw materials: 65 to 75 wt.% SiO2; 1 to 3 wt% Al2O3; 8 to 20 wt% Li2O; 1 to 8 wt % P2O5; and 2 to 8 wt. % ZrO2.
35. The method according to any one of claims 31 to 33, characterized in that Based on 100% by weight of the total amount of the composition, the precursor glass composition comprises the following raw materials: Greater than 0 to 10 wt. % CaO.
36. The method according to any one of claims 31 to 33, characterized in that Based on 100% by weight of the total amount of the composition, the precursor glass composition comprises the following raw materials: 2 to 10 wt.% CaO.
Citation Information
Patent Citations
Lithium disilicate-apatite glass-ceramic
US20150087493A1
Process for producing a sintered lithium disilicate glass ceramic dental restoration and kit of parts
WO2015200017A1